Types of Anxiety and Depression: Theoretical Assumptions and Development of the Anxiety and Depression Questionnaire - Fajkowska, Małgorzata; Domaradzka, Ewa; Wytykowska, Agata (Frontiers in Psychology, 2018)
The present paper is addressed to (1) the validation of a recently proposed typology of anxiety and depression, and (2) the presentation of a new tool – the Anxiety and Depression Questionnaire (ADQ) – based on this typology. Empirical data collected across two stages – construction and validation – allowed us to offer the final form of the ADQ, designed to measure arousal anxiety, apprehension anxiety, valence depression, anhedonic depression, and mixed types of anxiety and depression. The results support the proposed typology of anxiety and depression and provide evidence that the ADQ is a reliable and valid self-rating measure of affective types, and accordingly its use in scientific research is recommended.